In situ scanning electron microscopy study of fatigue crack propagation - Jacobsson, L.; Persson, C.; Melin, S. (Проблемы прочности, 2008)
The fatigue crack propagation rate is influenced by various mechanisms at the very vicinity of the crack tip, e.g., local plasticity and/or creep, microcracking, crack branching, and crack closure induced by plasticity and roughness. To study these mechanisms and their influence on crack propagation rate during different loadings, in situ scanning electron microscope studies have been performed. Throughout the load cycles images were taken and analyzed with an image analysis technique to measure the displacements around the crack tip. The obtained data can be used to determine compliance curves at any point along the crack, crack shapes, and the displacementfield in the crack tip vicinity. The technique has been used to analyze which mechanisms of crack propagation are realized during, e.g., fatigue with overloads, and thermomechanical fatigue. The results were compared with resultsfrom measurements using the direct currentpotential drop technique, and it was found that various load conditions promote different mechanisms for crack propagation.